Evaluating State-of-the-Art Computerized Pupillary Assessments for Glaucoma Detection: A Systematic Review and Meta-Analysis - Suo, Lingge; Zhang, Di; Qin, Xuejiao; Li, Annan; Zhang, Chun; Wang, Yunhong (Frontiers in Neurology, 2020)
Computerized pupillary light reflex assessment devices (CPLRADs) may serve as an effective screening tool for glaucomatous optic neuropathy, since they can dynamically detect abnormal pupillary responses from a novel sequence of light stimuli and functionally-shaped stimuli. The aim of this study was to systematically evaluate the current state of advanced CPLRADs and accuracy of application in detecting glaucoma. An electronic literature search of PubMed, MEDLINE, and Embase from database inception to December 2019 was performed. Studies that reported data on the use of computer-aided pupillometry with monocular and/or binocular monitoring in glaucoma patients were included. Two review authors independently conducted the study selection and extracted study data. A total of twenty-five studies were included in this review; eight studies with a total of 829 subjects were included in this meta-analysis. Data were pooled using a random-effect model, since the significant heterogeneity (P < 0.1, I2> 50%). Our meta-analysis of eight studies showed reasonably high summary sensitivity and specificity estimates of 0.81 (95% CI 0.73–0.89) and 0.83 (95% CI: 0.75–0.91), respectively. Simpler monochromatic devices, such as PupilmetrixTM PLR60, generally performed as well as or slightly better than more complex chromatic devices. This review suggests that CPLRADs may facilitate direct clinical decision making for glaucoma diagnosis and evaluation, and may provide a deeper understanding of the pathomechanism of glaucoma.